ADMINISTRATION OF LOCAL GOVERNMENT ORGANIZATIONS ACCORDING TO GOOD GOVERNANCE - Maneewanworawut, Amnat (Journal of MCU Nakhondhat, 2023)
These research objectives were as follows: 1) to study the level of effectiveness of good governance principles the administration of Local Administrative Organizations; 2) to study factors act on for applying good governance the administration of Local Administrative Organizations, and 3) Guidelines for applying good governance principles was used the administration of Local Administrative Organizations. This was a qualitative research. The data was collected using the In-Depth Interview. The interview for informant such as administration groups, policy groups, academic groups, stakeholders consisted of 18 people. Data was analyzed using summary. The results showed that. The problem of administration was inefficiency. It doesn’t the requirements of people in local, corruption. Good governance principles including The Rule of Law, Morality, Accountability, Participation, Responsibility and Cost – effectiveness or Economy to solve a problem. There were clearly regulations, to encourage virtues of religious. Act for performance. The people to participate and be economical it’s a factor that promotes administration according to good governance. Guidelines for applying good governance principles to the administration of Local Administrative Organizations, such as promoting the integration of people’s groups and a community, promoting the process of political participation, promoting the development of personnel in Local Government Organizations, senior official and political officials to strengthen the power to people and local communities and was considered a guideline for the performance of personnel in local government organizations for sustainable regional development.